Left ventricular surface kinematics as it fills and contracts - Yeo, Si Yong (2008)
It is hypothesized that myocardial ischemia and other cardiac pathologies are associated with regional alterations in ventricular shape. In order to elucidate and assess the left ventricular (LV) surface shape changes during the cardiac cycle, information regarding the surface properties is particularly useful. In this report, the differential properties of the LC surface were computed via an analytic approach using local surface fitting method. The efficiency of the proposed surface fitting algorithms was validated against exact solutions for simple geometrical shapes and was found to offer great accuracy in the computation of curvatures.